PENENTUAN SWELLING PRESSURE TANAH LEMPUNG EKSPANSIF MENGGUNAKAN ALAT GEONOR - , SEPTIANA SETTYORINI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Soil is home to the foundation of a building. However, the soil also has problems, one of which can inflate after suppressing (swelling pressure), which can damage buildings. The magnitude of the volume of dry weight (Î³d) and water content (É·) Different is a problem in determining the swelling pressure. This study will reveal how much the swelling pressure that owned the land. While the magnitude of swelling pressure tested using a Geonor Swelling Test Apparatus. The tools used in determining pressure development (swelling pressure) vary, such as oedometer, Konsolidometer, Geonor and so forth. However, in this study only uses Geonor tool, because this tool use ordinance no. The result is a tool module Geonor Swelling Test Apparatus, so the maximum value of swelling pressure can be determined. Swelling maximum pressure obtained was 79 gr/cm2 with 0% water content, the dry weight of the volume of 1.1 gr/cmÂ³ with clay soils high in soil samples from Ngawi, East Java.